2015
DOI: 10.2991/icaet-14.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scientific Literate Society: Status and Challenges

Abstract: -Building a scientific society is a necessary prerequisite for Malaysia in its attempt to be a developed and modern society based on science and technology. A scientifically literate society entails citizens who are literate in science and technology, and are able to make rational and objective decisions based on such knowledge for the society well-being. Besides being a consumer of scientific developments and innovations, a scientifically literate society requires a critical social mass that will ensure the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This finding is in line with the study carried out that revealed the lack of critical and creative thinking among postgraduate students [7]. This may due to the current education system in Malaysia is predominantly teacher centered and examination oriented [16], [17]. Little time has been spent on discussing the scientific ideas and interpreting the findings during the practical science class.…”
Section: Mastery Level Of Inventive Thinkingsupporting
confidence: 83%
“…This finding is in line with the study carried out that revealed the lack of critical and creative thinking among postgraduate students [7]. This may due to the current education system in Malaysia is predominantly teacher centered and examination oriented [16], [17]. Little time has been spent on discussing the scientific ideas and interpreting the findings during the practical science class.…”
Section: Mastery Level Of Inventive Thinkingsupporting
confidence: 83%